2014
DOI: 10.3233/jad-141365
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Children: Neural and Tight Junction Antibodies and Combustion Metals, the Role of Barrier Breakdown and Brain Immunity in Neurodegeneration

Abstract: Millions of children are exposed to concentrations of air pollutants, including fine particulate matter (PM2.5), above safety standards. In the Mexico City Metropolitan Area (MCMA) megacity, children show an early brain imbalance in oxidative stress, inflammation, innate and adaptive immune response-associated genes, and blood-brain barrier breakdown. We investigated serum and cerebrospinal fluid (CSF) antibodies to neural and tight junction proteins and environmental pollutants in 139 children ages 11.91 ± 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 146 publications
2
77
0
Order By: Relevance
“…In the setting of urban air pollution, the evolution of a changing paradigm favoring a pathogen penetrating an epithelial lining and via transsynaptic transmission reaching preganglionic parasympathetic motor neurons of the vagus nerve [63] has to entertain environmental swallowed particulate matter as a potential culprit. We suggested that damage to epithelial and endothelial barriers associated to air pollution exposures is a robust trigger of tight junction and neural antibodies [31]. Cryptic 'self' tight junction antigens can trigger an autoimmune response potentially contributing to the neuroinflammatory and Alzheimer and Parkinson's pathology present in megacity children.…”
Section: Breakdown Of Epithelial and Endothelial Barriers: No Barriermentioning
confidence: 99%
See 2 more Smart Citations
“…In the setting of urban air pollution, the evolution of a changing paradigm favoring a pathogen penetrating an epithelial lining and via transsynaptic transmission reaching preganglionic parasympathetic motor neurons of the vagus nerve [63] has to entertain environmental swallowed particulate matter as a potential culprit. We suggested that damage to epithelial and endothelial barriers associated to air pollution exposures is a robust trigger of tight junction and neural antibodies [31]. Cryptic 'self' tight junction antigens can trigger an autoimmune response potentially contributing to the neuroinflammatory and Alzheimer and Parkinson's pathology present in megacity children.…”
Section: Breakdown Of Epithelial and Endothelial Barriers: No Barriermentioning
confidence: 99%
“…Continuous expression of potent inflammatory mediators in the CNS and the formation of reactive oxygen species (ROS) are major findings in urban residents. Ultrafine PM (UFPM), PM-LPS, and metal uptake take place through olfactory neurons, cranial nerves such as the trigeminal and vagus, the GI tract, the systemic circulation, and macrophage-like cells loaded with PM from the lungs [31][32][33][34][35][36].…”
Section: Neuroinflammatory and Neurodegenerative Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term air pollution in cities relates to neuroinflammation, an altered innate immune response, disruption of the blood-brain barrier, ultrafine particulate deposition, and accumulation of beta-amyloid in children and young adults [290]. Air pollution also disrupts epithelial and endothelial barriers and triggers autoimmune responses involving tight junction and neural autoantibodies [291].…”
Section: Cosmetic Ingredients Targeting Autism Genesmentioning
confidence: 99%
“…In another study carried out on 50 Mexico City Metropolitan Area (MCMA) children having ages 13.4 ± 4.8 years on urban air pollution reveled decreased attention, short-term memory, and below-average levels of intelligent quotient [20]. A different study performed in the same area (MCMA), 139 children having ages 11.91 ± 4.2 year were reported [21] to show an early brain imbalance in oxidative stress, inflammation, innate and adaptive immune response-associated genes, and BBB breakdown from exposures of urban air pollution. Air pollution was shown [22] to adversely affect the cognitive-function and-performance in elderly women, in which the impact of the traffic exposure was significant to those carrying the apolipoprotein E (APOE) ε4 allele the most prevalent genetic risk for AD.…”
Section: Introductionmentioning
confidence: 97%